Mechanisms of Copper-Induced Autophagy and Links with Human Diseases - Yuanyuan Fu; Shuyan Zeng; Zhenlin Wang; Huiting Huang; Xin Zhao; Min Li (Pharmaceuticals)
As a structural and catalytic cofactor, copper is involved in many biological pathways and is required for the biochemistry of all living organisms. However, excess intracellular copper can induce cell death due to its potential to catalyze the generation of reactive oxygen species, thus copper homeostasis is strictly regulated. And the deficiency or accumulation of intracellular copper is connected with various pathological conditions. Since the success of platinum-based compounds in the clinical treatment of various types of neoplasias, metal-based drugs have shown encouraging perspectives for drug development. Compared to platinum, copper is an essential intracellular trace element that may have better prospects for drug development than platinum. Recently, the potential therapeutic role of copper-induced autophagy in chronic diseases such as Parkinson’s, Wilson’s, and cardiovascular disease has already been demonstrated. In brief, copper ions, numerous copper complexes, and copper-based nano-preparations could induce autophagy, a lysosome-dependent process that plays an important role in various human diseases. In this review, we not only focus on the current advances in elucidating the mechanisms of copper or copper-based compounds/preparations on the regulation of autophagy but also outline the association between copper-induced autophagy and human diseases.